The impact of loose coupling on police effectiveness - Knight, Gavin M. (The Australian and New Zealand journal of criminology, 2017)
This paper discusses loose coupling within police organisations, and the implications for police effectiveness. It uses findings from a qualitative study involving semi-structured interviews of 121 personnel from New Zealand Police and Queensland Police Service. The study provided insights into the characteristics of loose coupling in police agencies. The paper discusses the implications of these characteristics for the effectiveness of police. It suggests that the perceptions employees hold of the performance management practices that police use influence the extent of loose coupling. This loose coupling has both positive and negative effects. It reduces the ability of senior management to control the behaviour of employees. However, lack of management control does not result in an organisational culture that tolerates poor performance. The study found that strong peer pressure exists within workgroups to support the team and show commitment to doing a good job.